2008
DOI: 10.1177/0894318408314698
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Developing the Health Promotion Model in Low-Income, Korean Elderly Women

Abstract: This study was conducted to test Pender's health promotion model in low-income, Korean elderly women. A total of 389 low-income, Korean elderly women completed the interviews focused on the concepts in health promotion model. Seventy-three percent of the variance in health-promoting behaviors was accounted for by prior health-related behavior, biological, psychological, and sociocultural factors, behavior-specific cognitions and affect, environmental influences, commitment to a plan of action, and health-promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In this study, HPBs were meaningfully and positively associated with prior health-related behaviours. This result was in line with that of previous researches [12], [30]. Pender proposed that prior related behaviour had direct and indirect influences on existing HPBs as they could lead to changes in present health-related behaviours and inspire habitual participation in HPBs, even without attention to individual behaviours [1].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, HPBs were meaningfully and positively associated with prior health-related behaviours. This result was in line with that of previous researches [12], [30]. Pender proposed that prior related behaviour had direct and indirect influences on existing HPBs as they could lead to changes in present health-related behaviours and inspire habitual participation in HPBs, even without attention to individual behaviours [1].…”
Section: Discussionsupporting
confidence: 92%
“…Lee et al stated that self-efficacy positively correlated with health behaviours in mothers with infants and toddlers [33]. Also, Shin et al showed that perceived self-efficacy had direct effects on HPBs in elderly Korean women [30].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was partly in line with that of Bahmanpour (2011) in which all the HPM variables were statistically significant predictors of oral health behavior, explaining 42.2% of the variance (35). The results of Shin’s (2008) study indicated that prior health-related behavior, biological, psychological, and sociocultural factors, behavior-specific cognition and impacts, environmental influences, and commitment to a plan of action were the variables that justified 73% of the variance in health-promoting behaviors (36). Notwithstanding, sample size and the target population could have caused these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals will change their motivation for pursuing health-promoting behaviours due to perceived behavioural benefits, behavioural barriers, self-efficacy and activity-related effects [20]. Studies have shown that about 73% of behavioural changes can be predicted by components of Pender's HPM [26]. At present, Pender's HPM has achieved positive application in terms of health behaviours in chronic diseases, such as coronary heart disease [27,28], hypertension [29], haemodialysis [30] and diabetic foot ulcers [31], as well as within the general population.…”
Section: Discussionmentioning
confidence: 99%